Hati-hati, Ini Konsekuensi Hukum Jika Tugas Akhir Dikerjakan Orang Lain - Lubis, Muhammad Ridwan (UNES Law Review, 2024)
The phenomenon of thesis jockeying has become a subject of intense scrutiny due to the confluence of several complex factors: an educational culture that places a high premium on final results, the mental attitudes of students, and the absence of robust regulatory frameworks. In certain cities, the mushrooming of thesis writing services has posed a significant challenge to the very existence of universities. This practice has been denounced as immoral and a form of intellectual fraud. The objective of this research is twofold: to investigate the criminal law implications of final assignments in higher education and to evaluate the criminal law policies pertaining to thesis writing services in the context of future developments. This study employed a normative legal method for analysis, which entailed an in-depth review of relevant laws and regulations, as well as an examination of the underlying legal principles. The findings revealed two primary conclusions. First, while the criminal law aspect of final project writing services may be deemed unethical, they cannot be charged with fraud as defined in the Criminal Code of Ukraine. This is due to the fact that the elements of fraud, as defined under this legal framework, were not met. The principle of legality in criminal law, as articulated in Article 1 of the Criminal Code of Ukraine, requires that a person be punished only in the presence of a clear legal basis. While the act of providing final project writing services may be considered reprehensible, it does not constitute criminal conduct, and as a result, no criminal sanctions can be applied. Secondly, criminal law policy must aim to prevent crime. Criminal sanctions represent one of the instruments employed in this effort.